"Knowledge Regarding Consanguineous Marriage And Its Genetic Effects Among Young Adults At Selected Colleges: A Descriptive Study." (Journal of Pharmaceutical Negative Results, 2022)
Background - According to the March of Dimes (MOD) annual world reports of birth defects in millions of births (6% of total births), 94% of these births were in middle- and low-income countries. According to a joint WHO-MOD meeting report, the prevalence of birth defects accounts for 7% of all neonatal mortality and 3.3 million under-five deaths. The most common birth defects in India are found at 6-7%, which translates to about 1.7 million birth defects per year. Various birth defects include congenital heart disease (8-10 per 1000 live births), congenital deafness (5.6-10 per 1000 live births) and neural tube defects (4-11.4 per 1000 live births)). Some congenital anomalies are found after birth, others may not be diagnosed until later in life. A structural defect such as spina bifida is clear at birth, whereas hemophilia as a functional defect (bleeding disorder) is not usually apparent until infancy or childhood.Objective-.1 To assess the knowledge regarding Consanguineous Marriage and its Genetic Effects among young adults in selected colleges.2. To determine the association between knowledge scores and selected demographic variables.Methodology - Descriptive design. Use for studying. Over 100 young adults were surveyed using a non-probability appropriate sampling technique. The results were evaluated using a self-structured knowledge questionnaire for knowledge. The analysis shows that the mean knowledge score was 16.66 ± 3.83 and the mean percentage of knowledge was 55.53 ± 12.89. The study revealed that average knowledge 21-40% (7-12) Excellent 81-100% (25-30) regarding consanguineous marriage and its genetic effects. It also showed a significant association of knowledge of consanguineous marriage, its genetic effects Age, Gender, Occupation of parents at 0.05 level of significance (P <0.05).Conclusion- The study concluded that there is an association of knowledge score with age, sex, occupation of parents, there is an association of knowledge score with age, sex, occupation of parents at p <0.05 level of significance. None of the other demographic variables were associated with knowledge scores. The study also revealed that young adults had good knowledge of consanguineous marriage, but not adequate knowledge of genetic effects.